Reconstructing trauma and recovery: life narratives of survivors of political violence during apartheid - Rogobete, Ileana Carmen (Department of Psychology, 2015)
The central aim of this study was to examine the narratives of survivors of political violence during apartheid and their complex ways of reconstructing trauma and recovery, almost twenty years after the collapse of apartheid in South Africa. The traumatic events experienced by victims occurred during 1960 - 1993. This retrospective study involved victims of both sides of the conflict. The sample comprised twenty survivors of gross human rights violations who suffered: detention, torture, police harassment, displacement, shootings, or the loss of a significant other. Interviews were conducted between late 2009 and early 2010, involving participants from a diversity of race groups, ages, gender and socio-economic status. General areas of exploration were: (hi)story of suffering under apartheid, impact of traumatic events, ways of coping with negative effects, helpful and hindering aspects of their journey after trauma, present situation and views about the future. Interviews were recorded and transcribed for analysis.